Biological sex VS. Archaeological Gender: Enamel peptide analysis of the horsemen of the Early Middle age necropolises of Campochiaro (Molise, Italy). (February 2022) - Gasparini, Anthony; Lugli, Federico; Silvestrini, Sara; Pietrobelli, Annalisa; Marchetta, Isabella; Benazzi, Stefano; Belcastro, Maria Giovanna
Highlights: Unique burial context of the Early Medieval necropolises of Campochiaro (Italy) Comparison between biological sex and archeological gender. Poor preservation of human skeletons and sex estimation. Amelogenin analysis and sex estimation. Cemetery structure and social organization. Abstract: Sex estimation of human skeletons may present difficulties, especially in relation to their state of preservation or to weak sexual dimorphism. This leads to reliance on gendered grave goods, giving rise to potential issues related to the social role and condition of the individual and the relationship with the community. We aimed at examining skeletal remains from two VII century CE necropolises (Vicenne and Morrione) from Campochiaro in Molise (Italy), characterized by the presence of burials of "horsemen, " warriors buried with horse in the same pit, the analyses of which showed some uncertainty in sex estimation with the common morphological methods. Thus, we analyzed the tooth enamel peptides of fifteen individuals for the presence of sexually dependent variants of the protein amelogenin. Sex estimation was possible in all the individuals examined. Individuals with male gendered grave goods were all confirmed to be male, while individuals without gendered grave context had sex estimated for the first time. Biological sex, archeological gender, and the gendered division of society have been confirmed to be strongly linked in this particular community. Further studies should be undertaken to better understand the ethnic and migratory aspects of this relevant funerary context.